PELAYANAN BIMBINGAN MANASIK HAJI PADA PT ARMINAREKA PERDANA BALIKPAPAN - Stella Dewi Rita; Siti Umaroh Rahayu (Multazam : Jurnal Manajemen Haji dan Umrah, 2022)
Every year, rituals are performed to prepare Indonesian pilgrims to perform the pilgrimage to Saudi Arabia during the hajj season. This is where the organizers of the pilgrimage, both government and private, become the organizers of the guidance of rituals. The pilgrims must do the right practice in accordance with the rules that have been set according to Islamic teachings. The results of this study indicate that PT. Arminareka Perdana has carried out Hajj guidance services to the maximum extent possible. This is measured in terms of planning, implementation, and evaluation of the good results that have been carried out by PT. Arminareka Perdana. Coupled with the addition of the number of pilgrims who joined PT. Arminareka Perdana makes the writer believe that the services provided by PT. Arminareka Perdana has been very good.